Azoreductase activity in intact cells of a non-conventional yeast strain - Ramalho, Patrícia A. (2002)
Poster apresentado no Annual Workshop COST 847 Textile Quality and Biotechnology, 2, Villa Olmo, Como, Itália, 10-11 Outubro 2002.